A non-linear model of solid-state amorphization - Demishev, S; Ischenko, T; Blundell, S; Singleton, J (1997)
A non-linear model of solid-state amorphization (SSA) is proposed which takes into account the interaction of the structural elements of the amorphous phase via a stress field. For the experimental parameters which correspond to semiconductors undergoing SSA by high-pressure phase retention, we obtain the solution in the form of a self-sustaining wave with a constant velocity v. This solution exists in the region v < vc, where the critical velocity vc is controlled by the thermal and concentration diffusivities DT and DN . A simple scaling relation is proposed for vc: vc(DN, DT) ∼ DT/(DN)0.5. It is found that the characteristic correlation length of the amorphous phase formed by SSA strongly depends on the interplay between the parameters v, DN and DT.